Fertility and the household's economic status: A natural experiment using Indian micro data - Nabanita Datta Gupta and Amaresh Dubey (Journal of Development Studies, Vol. 42, No. 1, 110-138, January 2006, 2006)
We model fertility as endogenous to the family's economic status because poor households choose to have large families in the absence of adequate social insurance. Because of a strong son preference in India, having two girls first can proxy an exogenous increase in fertility, and is therefore a good instrument for fertility in determining poverty of rural households. The 1993-1994 Indian Quinquennial Survey data shows that even though poverty rates are comparable, 74 per cent of two-girl families have a third child compared to 63 per cent ofother families. Fertility significantly positively affects poverty when treated as exogenous, butvanishes once endogenised. These results are robust to omitting states with skewed sex ratios and to proxying economic status by expenditures.